Forest Conservation And Rehabilitation In Flood Hazard Reduction Experiences From USA China And Malaysia. - Chang, Ngai Weng; Zakaria, Nor Azazi; Ghani, Aminuddin Ab; Kung, Hsiang-Te (USM, 2006)
Increasing incidence of floods in recent decades in many countries, particularly the USA, China and Malaysia have been largely attributed to loss of natural water retention systems such as forest ecosystetns.